2014
DOI: 10.1002/14651858.cd003350.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Pain management for sickle cell disease in children and adults

Abstract: Pain management for sickle cell disease in children and adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 43 publications
1
13
0
Order By: Relevance
“…Pain episodes or crises may occur unpredictably (Fosdal & Wojner-Alexandrov, 2007) and are the most common reason for hospital visits (Yusuf, Atrash, Grosse, Parker, & Grant, 2010). Adults with SCD average over 197,000 emergency department visits annually; 67% of patients report pain as the reason for the emergency department visit and 29% result in hospital admissions (Yusuf et al), with 90% of the admissions being for the treatment of acute pain (Dunlop & Bennett, 2009). Management of this chronic disease occurs primarily at home and includes a strong emphasis on self-care across the lifespan.…”
Section: Introductionmentioning
confidence: 99%
“…Pain episodes or crises may occur unpredictably (Fosdal & Wojner-Alexandrov, 2007) and are the most common reason for hospital visits (Yusuf, Atrash, Grosse, Parker, & Grant, 2010). Adults with SCD average over 197,000 emergency department visits annually; 67% of patients report pain as the reason for the emergency department visit and 29% result in hospital admissions (Yusuf et al), with 90% of the admissions being for the treatment of acute pain (Dunlop & Bennett, 2009). Management of this chronic disease occurs primarily at home and includes a strong emphasis on self-care across the lifespan.…”
Section: Introductionmentioning
confidence: 99%
“…Large‐scale inpatient therapeutic studies for SCD have historically been difficult to complete . Currently available data are limited, studies often underpowered, and results sometimes difficult to interpret . Poor patient enrollment has been cited as major limitations in most studies .…”
Section: Discussionmentioning
confidence: 99%
“…Despite noteworthy advances in the management of other comorbidities of SCD and significant progress in the understanding of the pathophysiology of VOC , little has changed in the management of acute SCD pain in recent decades. Current management is based primarily on expert opinion , with evidence‐based acute management derived from small, often inadequately powered SCD‐specific studies or studies of non‐SCD pain . Robust multi‐center clinical trials for VOC are few in number and recent attempts have been plagued with multiple challenges leading to poor patient enrollment .…”
Section: Introductionmentioning
confidence: 99%
“…These are consistent in recognizing the paucity of clinical trial data, and the need to develop robust guidelines that are regularly audited on a local level. A Cochrane review (Dunlop & Bennett, ) highlighted the need for a standardized protocol of pain management as the basis for a control arm in future randomized controlled trials (RCTs) and recommended standardized measures of pain intensity and pain relief to facilitate comparison between studies. A recent NICE clinical guideline (NICE, ) has noted limited evidence on the effectiveness of different opioid protocols and has recommended conducting RCTs to compare different drugs, formulations and routes of administration.…”
Section: Evidence Base For Apc Managementmentioning
confidence: 99%
“…Admission to hospital with an acute complication is a frequent experience for patients with SCD, and it is important that patients’ views are taken into account in developing a management protocol for APC. The Cochrane Review of pain management suggested it would be useful to develop measures that quantify outcomes of relevance to patients and families (Dunlop & Bennett, ).…”
Section: Patient Experiencesmentioning
confidence: 99%